2021
DOI: 10.1177/00375497211025495
|View full text |Cite
|
Sign up to set email alerts
|

Experiment, model, and simulation of the pedestrian flow around a training school classroom during the after-class period

Abstract: In China, training schools are ubiquitous, where heterogeneous pedestrian flow (which consists of adults and children) widely occurs during the after-class period. In this paper, we develop a fine grid cellular CA model to describe the pedestrian behaviors (e.g., pick-up behavior, searching behavior, matching behavior, waiting behavior, leading behavior, and following behavior) at a training school during the after-class period and explore the effects of the special behaviors on each pedestrian’s movement in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…In modeling and simulating evacuation scenarios, it is essential to take account of the crowd’s behavior and diverse emergency scenarios as pointed out by Wirz et al 38 Examples of several recent research works on diverse emergency evacuation scenarios are featured such as in metro station, 13 terminal apron, 39 training school, 40 and also during dense crowd. 41 Xie et al 13 proposed a stabilized coupled model of agent behavior and computational fluid dynamics model for effectiveness investigation of the fire evacuation in a metro station.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In modeling and simulating evacuation scenarios, it is essential to take account of the crowd’s behavior and diverse emergency scenarios as pointed out by Wirz et al 38 Examples of several recent research works on diverse emergency evacuation scenarios are featured such as in metro station, 13 terminal apron, 39 training school, 40 and also during dense crowd. 41 Xie et al 13 proposed a stabilized coupled model of agent behavior and computational fluid dynamics model for effectiveness investigation of the fire evacuation in a metro station.…”
Section: Related Workmentioning
confidence: 99%
“…The proposed work was effective in solving the rezoning of the Roll-on/Roll-off/ Passenger (Ro-Pax) terminal apron and the results showed that rational traffic organization and refined arrangement in the terminal apron can reduce the traffic hazards effectively. Xie et al 40 developed a fine grid cellular CA model to describe the pedestrian behaviors specifically adult–child behaviors and movement in the corridor during after-class periods at training schools. Hesham and Wainer 41 proposed a model based on centroidal particle dynamics considering the pedestrians’ close-range interactions in dense crowds.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Congestion is quite common and has attracted the attention of many researchers. Specifically, the impacts of different factors, including the locations of exits, 2 the internal layout of the system, 3 short-range collision avoidance, 4 pedestrian age, 5 an imbalanced initial layout of pedestrians, 6 and the kinship effect, 7 on congestion evacuation have been explored. However, these studies did not consider the impact of pedestrians’ visual attention-shifting behavior on congestion.…”
Section: Introductionmentioning
confidence: 99%
“…pick-up behavior, searching behavior, matching behavior, waiting behavior, leading behavior, and following behavior) at a training school during the after-class period was developed. 12 In terms of safety design and management of subway stations, researchers have proposed several engineering design and hand calculation methods for fire evacuation scenarios. [13][14][15] The emergency resource allocation and emergency response time were analyzed with a Petri net-based approach.…”
Section: Introductionmentioning
confidence: 99%